Parents' Worries about Life Problems of Adolescent Girls with Diabetes: a Qualitative Study - M Hemmati Maslakpak; F Ahmadi; A Feizi (Tehran University of Medical Sciences, 2011)
Background & Aim: Parents participation in management of diabetes has been recognized to be beneficent. Recognizing parents' worries should be addressed to plan effective health promoting programs. This study aimed to explore parents' worries about life problems of adolescent girls with diabetes. Methods & Materials: In this qualitative study, 26 parents (16 mothers and 10 fathers) of adolescent girls with type 1 diabetes were recruited using purposive sampling from the Diabetes Society in west Azerbaijan. Data were collected using in-depth and semi-structured interviews. Analysis of the transcripts was guided by qualitative content analysis. Results: Qualitative content analysis demonstrated three original categories from parents' worries: 1) worries about the future; 2) worries about the treatments; and 3) worries about the society. Conclusion: Better perception of parents' concerns may promote effective communication between health professionals and parents. Modification of parents' personal control and perceived threat through appropriate educational programs that acknowledge and address their concerns may be a means of empowering parents.   Key words: parents concerns, diabetes mellitus, girl adolescents, parents, qualitative research